An Investigation into Intuitionistic Logic with Identity - Chlebowski, Szymon; Leszczyńska-Jasion, Dorota (Bulletin of the Section of Logic, 2019)
We define Kripke semantics for propositional intuitionistic logic with Suszko’s identity (ISCI). We propose sequent calculus for ISCI along with cut-elimination theorem. We sketch a constructive interpretation of Suszko’s propositional identity connective.